Gene flow between chromosomal forms of the malaria vector Anopheles funestus in Cameroon, Central Africa, and its relevance in malaria fighting - (:unkn) unknown (My University, 2005)
Knowledge of population structure in a major vector species is fundamental to an understanding of malaria epidemiology and becomes crucial in the context of genetic control strategies that are being developed. Despite its epidemiological importance, the major African malaria vector Anopheles funestus has received far less attention than members of the Anopheles gambiae complex. Previous chromosomal data have shown a high degree of structuring within populations from West Africa and have led to the characterization of two chromosomal forms, “Kiribina” and “Folonzo.” In Central Africa, few data were available. We thus undertook assessment of genetic structure of An. funestus populations from Cameroon using chromosomal inversions and microsatellite markers. Microsatellite markers revealed no particular departure from panmixia within each local population and a genetic structure consistent with isolation by distance. However, cytogenetic studies demonstrated high levels of chromosomal heterogeneity, both within and between populations. Distribution of chromosomal inversions was not random and a cline of frequency was observed, according to ecotypic conditions. Strong deficiency of heterokaryotypes was found in certain localities in the transition area, indicating a subdivision of An. funestus in chromosomal forms. An. funestus microsatellite genetic markers located within the breakpoints of inversions are not differentiated in populations, whereas in An. gambiae inversions can affect gene flow at marker loci. These results are relevant to strategies for control of malaria by introduction of transgenes into populations of vectors.
Keywords: African Research